Implementing family involvement in the treatment of patients with psychosis: a systematic review of facilitating and hindering factors - Eassom, Erica (BMJ Publishing Group, 2014)
OBJECTIVE: To synthesise the evidence on implementing family involvement in the treatment of patients with psychosis with a focus on barriers, problems and facilitating factors. DESIGN: Systematic review of studies evaluating the involvement of families in tripartite communication between health professionals, ‘families’ (or other unpaid carers) and adult patients, in a single-family context. A theoretical thematic analysis approach and thematic synthesis were used. DATA SOURCES: A systematic electronic search was carried out in seven databases, using database-specific search strategies and controlled vocabulary. A secondary manual search of grey literature was performed as well as using forwards and backwards snowballing techniques. RESULTS: A total of 43 studies were included. The majority featured qualitative data (n=42), focused solely on staff perspectives (n=32) and were carried out in the UK (n=23). Facilitating the training and ongoing supervision needs of staff are necessary but not sufficient conditions for a consistent involvement of families. Organisational cultures and paradigms can work to limit family involvement, and effective implementation appears to operate via a whole team coordinated effort at every level of the organisation, supported by strong leadership. Reservations about family involvement regarding power relations, fear of negative outcomes and the need for an exclusive patient–professional relationship may be explored and addressed through mutually trusting relationships. CONCLUSIONS: Implementing family involvement carries additional challenges beyond those generally associated with translating research to practice. Implementation may require a cultural and organisational shift towards working with families. Family work can only be implemented if this is considered a shared goal of all members of a clinical team and/or mental health service, including the leaders of the organisation. This may imply a change in the ethos and practices of clinical teams, as well as the establishment of working routines that facilitate family involvement approaches.